Relative costs of new water supply options for Front Range cities: phase 2 report - Kenney, Douglas S., author; Mazzone, Michael, author; Bedingfield, Jacob, author; Bergemann, Crystal, author; Jensen, Lindesy, author (Colorado State University. Libraries, 2011)
The following report is the second (and final) installment of a project examining the costs associated with meeting future M&I (municipal and industrial) water supplies along Colorado's Front Range. As summarized in the recently updated Statewide Water Supply Initiative (SWSI 2010) reports, M&I water demand in Colorado is expected to climb by 600,000 to one million AF (AF) by 2050 (CWCB, 2010). Some mixture of three strategies will likely be necessary to meet this target: new water projects, water transfers (i.e., agricultural to urban reallocation), and conservation. Determining which option(s) is "best" is a complex matter that requires weighing highly case-specific opportunities, constraints, trade-offs, risks, uncertainties, and values. Presumably, among the most important considerations is economic cost. In this Phase 2 report, we continue our consideration of what is known and unknown about the economic costs of meeting these future water demands.
June 2011.
Prepared for the Colorado Water Conservation Board and the Colorado Water Institute.
Published as part of the Western Water Policy Program at the University of Colorado's Natural Resources Law Center.
Keywords: Water-supply -- Front Range (Colo. and Wyo.); Water-supply -- Front Range (Colo. and Wyo.) -- Costs